Literature Review: The Role of Psychological Capital among Indonesian’s Worker - Unika Prihatsanti (Universitas Ahmad Dahlan, 2017)
AbstractPsychological capital is a positive psychological state, characterized by having self-efficacy, hope, optimism, and resiliency. The findings show that psycap plays a vital role in the emergence of positive behaviors at the workplace. This study aims to conduct a literature review on the role of psychological capital in workers from various settings in Indonesia. The literature search is done through portalgaruda.org and onesearch.id database using the keywords